2018
DOI: 10.1007/s13595-018-0758-y
|View full text |Cite
|
Sign up to set email alerts
|

An integrated method for high-resolution definition of new diameter-based fine root sub-classes of Fagus sylvatica L.

Abstract: & Key message Compared to the traditional approach, applying micrometric image analysis to fine root samples of Fagus sylvatica with subsequent data treatment through principal component and cluster analysis yielded specific diameter sizes for fine root sub-classes having better resolution of the corresponding branching orders, and a more coherent relationship with the values of annual production and turnover rate. & Context Fine root traits are poorly understood, impeding an accurate representation of terrest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 76 publications
1
20
0
Order By: Relevance
“…The double peaks of root growth were the manifestation of the completion of the above-ground biomass of the trees and the beginning of more resource allocation to the root system. Previous studies indicated that the peak of root growth patterns was partly attributed to the phenology of the trees [27,30] in response to soil moisture, nutrient acquisitions, and other growth-promoting factors [7,17,27].The current study indicated that the trees Ca and Ca and Mg combined nutrients had a positive impact on the FRLD dynamics; while Mn and Zn had also a significant effect on FRLD with emphasis on root-zone soil pH management. The decline in FRLD and yield was partly attributed to HLB-induced damage of fine roots, which led to vulnerability to other biotic and abiotic stresses [1,12,15].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The double peaks of root growth were the manifestation of the completion of the above-ground biomass of the trees and the beginning of more resource allocation to the root system. Previous studies indicated that the peak of root growth patterns was partly attributed to the phenology of the trees [27,30] in response to soil moisture, nutrient acquisitions, and other growth-promoting factors [7,17,27].The current study indicated that the trees Ca and Ca and Mg combined nutrients had a positive impact on the FRLD dynamics; while Mn and Zn had also a significant effect on FRLD with emphasis on root-zone soil pH management. The decline in FRLD and yield was partly attributed to HLB-induced damage of fine roots, which led to vulnerability to other biotic and abiotic stresses [1,12,15].…”
Section: Discussionmentioning
confidence: 52%
“…Ca nutrition for trees budded on Cleo and Ca and Mg combined nutrient treated trees budded on Swc rootstocks significantly improved the FRLD of fine roots d > 1 mm. The variation in FRLD density was associated with the growth flush growth stage [7,17,29], moisture [16,17,30], and fertilization [17,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Menzel & Fabian, 1999;Jeong et al, 2011). The average biomass of finest roots <1 mm was estimated from the fine root biomass measured for the organic layer and top mineral soil (see subchapter on 'Root morphology and root biomass' section below) and the distribution of beech fine roots into diameter subclasses according to Montagnoli et al (2018) (59% of fine roots in <1 mm class).…”
Section: Researchmentioning
confidence: 99%
“…Fine root form and function may differ among branching orders [38,39] and the shortcomings of the diameter-based approach are widely recognized [40]. Therefore, in this study, the size class approach was maintained for a better discrimination between the <0.5 mm diameter class (i.e., very fine roots), which represent the most dynamic component of the root system, and the 0.5-1 and 1-2 mm diameter classes, which represent the more stable and woodier portion [41][42][43].…”
Section: Introductionmentioning
confidence: 99%